(untitled) (Fiep Bulletin - online, 2020)
Through a mythological-theological critic of struggle and overcoming in sport, we pretend to defend a thesis based on suffering as an educational formative process, as a human development process, either in a institutionalized environment, such as schools, or not. Howsoever it is important to clarify that suffering does not refer to punishment, physical violence or common sense suffering, it means the little (or not) frustrations understood by Freud in his sexual theory, libido, theory of pleasure, as part of human development (LASTÓRIA, 2017a). By critique, we understand “the denial of the established norm, the anti-positivism, the search for a fairer and more humane society.” (PUCCI, 2017, p.01). The “mythological-theological” will be based in authors from the DEI school of secular theology (Department of Ecumenical Investigation, in San Jose, Costa Rica). For being ambiguous, struggle and suffering in sport can reproduce the same mythical-religious sacrificial foundation demanded by neoliberal capitalism overconsumption, an unethical, fatalistic, hedonistic, selfish foundation, or promote the construction of a resilient personality, a fighter personality, a human being.